Construction waste management in the green accounting perspective: a study on construction companies in Indonesia / Hedy Desiree Rumambi ... [et al.] - Rumambi, Hedy Desiree; Willar, Debby; Ramschie, Ali Akbar Steven; Senduk, Novatus; Tulung, Fransiscus Josep (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study describes construction waste management activities and their relevance to financial statement elements from a green accounting perspective. The research used a qualitative approach and was conducted on nine small and medium enterprise construction service companies with K (small) and M (medium) business scales. Data were collected using in-depth interviews with 17 informants and analysed using the Miles and Huberman technique. The results showed that the cost of managing concrete waste was part of the cost of cleaning the project site and had a 2-5% budget of the total. A concrete waste crusher machine will have a positive impact on the company because the results of waste treatment can be used in other construction processes. Reducing, reusing, recycling, and landfilling are all construction waste management activities. These activities have an impact on the cost of economic resources and the economic and environmental benefits for the company. These sacrifices and benefits are relevant to the elements that make up environmental financial statements. These elements include fixed assets (recycled machines and equipment), environmental costs, social costs, and other income, representing economic and environmental phenomena from construction waste management activities and is becoming a concern for green accounting implementation in construction companies in developing countries.